Pendidikan Kritis Mansour Fakih: Sudut Pandang Pendidikan Islam - Mochammad Ja’far Amri; Radino Radino (Nusantara: Jurnal Pendidikan Indonesia, 2022)
Education has a final orientation as a form of humanization, namely humanizing humans, and aims as a vehicle for liberation. One of the figures who brought this idea up was Mansour Fakih, a social activist who is aggressively voicing education from the point of view of the marginalized. This study uses qualitative research methods with the type of literature study. The results show that the idea of education with Mansour Fakih's critical paradigm can improve the domination structure which is considered inappropriate in the field of education by producing a critical perspective. A review of Islamic education can later have implications for education that eliminates aspects of class, humanist education, and critical ideas aligned with Islamic views. From these three concepts, it is hoped that education in Indonesia can be better in the future structurally and culturally so that it can become a vehicle for learning to think critically for the next generation of people who innovate with development.